ANALISIS KEMAMPUAN MENYIMAK SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Dina Aulia Yudistira Munthe; Trisna Pratiwi Hasibuan; Dinda Patliana Sukma; Syahrani Yumna Irfani; Yuli Deliyanti (Pusat riset dan Inovasi Nasional, 2023)
Language skills are needed for all individuals. This is because language skills are a model for developing students’ intellectual, social, and character abilities. The first language skill possessed by humans is listening. The purpose of writing this article is to analyze student listening skills in learning Indonesian at MI/SD. This research uses the library research method which is a series of activities related to the method of collecting library data, reading and recording and processing the research material. Listening is one of the most important language skills that must be mastered by students, but in reality many students do not like learning to listen. Most think that learning to listen is a boring lesson.